Tumors and Tumorlike Lesions of Bone Pathology, Radiology, and Treatment - Schajowicz, Fritz (Springer Berlin Heidelberg, 1994)
More than ten years have elapsed since the publication of the first edition of Tumors and Tumorlike Lesions of Bone and Joints in 1981. During this period significant progress has been made in diagnosis, and particularly in staging and treatment of bone tumors. In most centers, limb-sparing surgery has replaced the more radical ablative surgery, with or without preoperative chemotherapy. This became possible due to the introduction and increased application of newer high-quality imaging techniques (CT and MRI) and in particular the use of new cytomorphologic methods of diagnosis, especially immunohisto chemistry. These advances in diagnosis and treatment have been reflected by the publication of new editions of several important text books, since their authors - pathologists, orthopedic surgeons, and radiologists - felt the necessity of updating their works in recent years. However, in these publications different criteria of classification were adopted. The number of cases compiled at the Latin American Registry of Bone Pathology increased from 4913 primary bone tumors and more than 1100 tumorlike lesions at the time of publication of the first edition of this book, to 5274 bone tumors and 1665 tumorlike lesions by the end of December 1985, when I finished my work as head of the Registry and occupied the positions of Professor of Orthopedic Pathology at St. Louis University Medical Center and Distinguished Visiting Professor at Rush-Presbyterian-St. Luke's Medical Center in Chicago